Penerapan Media Berbasis IT untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas IV Sekolah Dasar - Tuerah, Roos M. S.; Tuerah, Jeanne M. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aimed to improve student learning outcomes in Mathematics class IV at Kinilow Catholic Elementary School through the application of IT-based media. The type of research used is Classroom Action Research. Data collection techniques are observation, tests and documentation. The subjects of this study were 10 students of class IV of Kinilow Catholic Elementary School. The results of the study show that the application of IT-based media can improve student learning outcomes. As for the first cycle, student learning outcomes obtained a percentage of 62.5%, then learning outcomes in cycle 2 obtained a percentage of 86.5%. Implementation of cycle 2 by perfecting things that are lacking in cycle 1, student learning outcomes experience a significant increase and are declared successful. Based on the results obtained, it can be concluded that the application of IT-based media can improve the learning outcomes of fourth grade students at Kinilow Catholic Elementary School